Profil Kemampuan Siswa dalam Menyelesaikan Soal Cerita Operasi Hitung Pecahan Ditinjau dari Perbedaan Jenis Kelamin - Dianra, Atmika Radifa; Anggraini, Anggraini; Hasbi, Muh.; Rochaminah, Sutji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to describe students' ability in solving story problems of fractional operations in terms of gender differences. This type of research is qualitative research conducted in class VII A of SMPN 15 Palu. The researcher chose 2 informants as test and interview subjects, namely one female student with high ability and one male student with high ability. The results of this study are 1) female students with high ability are able to understand the problem well, can compile a solution plan by providing detailed statements and are able to implement the solution plan and re-check the correctness of their explanations with different steps. 2) male students with high ability experience delays in understanding story problems are able to compile a solution plan but are less careful in implementing the solution plan. However, at the re-checking stage, male students are able to test the explanation with different steps so that they can correct their mistakes and find the right answer. The conclusion of this study is that there is a difference in the ability to solve story problems on operations regarding fractions between female and male students, female students with high ability can understand the problem, make a solution plan, and recheck the explanation well, while male students with high ability experience delays in understanding the problem, are less careful in implementing the plan, but can correct mistakes and find the right answer when checking again. Keywords: Ability, Story Problems, Fractions, Gender